Modern Farmer Enterprise : "One Hand Seed Planter" / Mohamad Faeez Norzah...[et.al] - Norzah, Mohamad Faeez; Mohd Kamal, Mohd Nazreen; Ismail, Nora Fazlin; Maulad Mazlan, Norshahira; Mohd Zainudin, Manisah (Faculty of Plantation and Agrotechnology, 2016)
Modem Farmers Enterprise is an existing company dedicated to the production of agricultural machinery. Our company has been form as the partnership company's among the member's shareholders and it located at Alor Gajah, Melaka. Modem Farmer Enterprise is working hard to become a leading producer of agricultural machinery for the supplies industry as well as in plantation.